2019
DOI: 10.14486/intjscs.2019.584
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Structured Physical Activity Intervention on Fundamental Motor Skills Development of Children with Mild and Moderate Autism Spectrum Disorder

Abstract: The children with Autism Spectrum Disorder (ASD) have impairment of gross motor skills. However, the motor deficiency is not a part of diagnosis of ASD. Majority of the people with ASD have motor imbalanced that affected serious health issues, body posture and PA performance. The major purposes of the study were to examine the impact of a structured physical activity programme on gross motor skills development on mild and moderate ASD. In order to achieve this purposes, the researcher has firmed two objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Researchers have shown that PA interventions are effective at improving motor competence of FMS of autistic children (Bremer et al, 2015; Colombo‐Dougovito et al, 2019; Healy et al, 2018; Muneer, 2019; Ruggeri et al, 2020). Even though findings from these interventions are promising, just a handful of these interventions included parents (Columna et al, 2021; Esentürk & Yarımkaya, 2021; Healy & Marchand, 2020; Yarımkaya et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that PA interventions are effective at improving motor competence of FMS of autistic children (Bremer et al, 2015; Colombo‐Dougovito et al, 2019; Healy et al, 2018; Muneer, 2019; Ruggeri et al, 2020). Even though findings from these interventions are promising, just a handful of these interventions included parents (Columna et al, 2021; Esentürk & Yarımkaya, 2021; Healy & Marchand, 2020; Yarımkaya et al, 2023).…”
Section: Introductionmentioning
confidence: 99%